2012
DOI: 10.1016/j.gene.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

DNA adenine methyltransferase (Dam) controls the expression of the cytotoxic enterotoxin (act) gene of Aeromonas hydrophila via tRNA modifying enzyme-glucose-inhibited division protein (GidA)

Abstract: Aeromonas hydrophila is both a human and animal pathogen, and the cytotoxic enterotoxin (Act) is a crucial virulence factor of this bacterium because of its associated hemolytic, cytotoxic, and enterotoxic activities. Previously, to define the role of some regulatory genes in modulating Act production, we showed that deletion of a glucose-inhibited division gene (gidA) encoding tRNA methylase reduced Act levels, while overproduction of DNA adenine methyltransferase (Dam) led to a concomitant increase in Act-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…To our knowledge, it is also the first description of an active bacteriophage-carrying MTase which methylates adenine residues in many various contexts. So far, enzymes with such an extremely relaxed substrate specificity have been only found in defective prophages and phage-related elements (Drozdz et al, 2012;Fang et al, 2012). Like in the case of other non-specific adenine MTases, ARM81ld_p56 activity was not detected in the lysogenic strain.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, it is also the first description of an active bacteriophage-carrying MTase which methylates adenine residues in many various contexts. So far, enzymes with such an extremely relaxed substrate specificity have been only found in defective prophages and phage-related elements (Drozdz et al, 2012;Fang et al, 2012). Like in the case of other non-specific adenine MTases, ARM81ld_p56 activity was not detected in the lysogenic strain.…”
Section: Discussionmentioning
confidence: 96%
“…Salmonella enterica serovar Typhimurium, Vibrio cholerae, Yersinia pestis, and Yersinia pseudotuberculosis (Heithoff et al, 1999;Julio et al, 2001;Robinson et al, 2005). It has also been shown that the dam gene is essential for the viability of A. hydrophila SSU and that M. AhySSUDam is involved in A. hydrophila pathogenesis (Erova et al, 2006a(Erova et al, , b, 2012. The putative Dam-like protein of Aeromonas sp.…”
Section: Functional Analysis Of the Dna Methylation Enzymes Of Farm81mentioning
confidence: 99%
“…In their study, a gidA deletion mutant was attenuated in mice due to a significant reduction in cytotoxic and hemolytic activity [58]. In a follow up study, Erova et al suggest act is under the regulatory control of both GidA and DNA adenine methyltransferase (Dam) and Dam regulates Act production via GidA [68]. Overall, these studies suggest GidA is part of a major regulatory pathogenic mechanism in Gram-negative bacteria.…”
Section: Virulence and Stress Responsementioning
confidence: 99%
“…In Myxococcus xanthus, deletion of gidA did not result in loss of motility as seen in other bacteria, but gidA deletion mutants were deficient in fruiting body development after several generations [13]. Finally, GidA was shown to significantly affect virulence in the emerging human pathogen Aeromonas hydrophila [58,68]. An initial study by Sha et al suggests GidA regulates the most potent virulence factor of A. hydrophila, the cytotoxic enterotoxin gene (act).…”
Section: Virulence and Stress Responsementioning
confidence: 99%
“…Of the 9, synaptosomal-associated protein 23 (SNAP23), galectin-3, and guanylate kinase 1 (GUK-1) were knocked down in murine macrophages and HT-29 epithelial cells (using small inhibitory RNA), with the former two resulting in reduced induction of apoptosis following Act exposure (Galindo et al, 2006a,b). Interestingly, we also observed that DNA adenine methyltransferase (Dam) and Glucose inhibited division protein (GidA) both work to positively influence act gene expression and its associated hemolytic activity (Erova et al, 2012). Interestingly, the Gram-positive pathogen, Staphylococcus aureus , also secretes a potent, pro-apoptotic enterotoxin, the superantigen enterotoxin B.…”
Section: Introductionmentioning
confidence: 99%